Charge-Assisted Halogen Bonding in an Ionic Cavity of a Coordination Cage Based on a Copper(I) Iodide Cluster - Peuronen Anssi; Taponen Anni I; Kalenius Elina; Lehtonen Ari; Lahtinen Manu (WILEY-V C H VERLAG GMBH, 2025)
The design of molecular containers capable of selectively binding specific guest molecules presents an interesting synthetic challenge in supramolecular chemistry. Here, we report the synthesis and structure of a coordination cage assembled from Cu3I4- clusters and tripodal cationic N-donor ligands. Owing to the localized permanent charges in the ligand core the cage binds iodide anions in specific regions within the cage through ionic interactions. This allows the selective binding of bromomethanes as secondary guest species within the cage promoted by halogen bonding, which was confirmed by single-crystal X-ray diffraction.